Novel bifunctional DATA chelator for quick access to site-directed PET 68Ga-radiotracers: preclinical proof-of-principle with [Tyr3]octreotide. Issue 42 (4th July 2017) - Nock, Berthold A.; Kaloudi, Aikaterini; Nagel, Johannes; Sinnes, Jean-Philippe; Roesch, Frank; Maina, Theodosia
Abstract : Comparison of 68 Ga-DATA-TOC vs . 68 Ga-DOTA-TOC in sst2 -positive cells and tumor-bearing mice revealed the suitability of DATA for easy access to 68 Ga-labeled vectors. Abstract : Molecular imaging of tumors with the PET radionuclide 68 Ga has gained momentum in clinical oncology due to the expanding availability of commercial 68 Ge/ 68 Ga-generators in combination with state-of-the-art PET/CT and PET/MRI hybrid imaging systems. Concurrently, interesting peptide-based or small-size vectors have been developed for theranostic use in cancer patients. Owing to the short half-life of 68 Ga ( t 1/2 = 67.7 min) and the sensitivity of many targeting biomolecules, labeling and kit reconstitution in mild conditions allowing for quick access to ready-for-injection PET-tracers are highly desirable. The novel DATA ((6-pentanoic acid)-6-(amino)methy-1, 4-diazepinetriacetate) chelator previously showing promising qualities for kit type labeling, was coupled to TOC ([Tyr 3 ]octreotide). We herein report results from a first proof-of-principle study directly comparing 67 Ga-DATA-TOC with the well-established 67 Ga-DOTA-TOC in a series of preclinical models. Both analogs were shown to be sst2 -preferring and specifically internalized in AR42J and HEK293-hsst2 cells, with 67 Ga-DOTA-TOC internalizing faster in both cell lines. Similarly, after injection in mice bearing either AR42J or HEK293-hsst2 tumors, both tracers efficiently and specifically localized in the implants. Whereas 67 Ga-DOTA-TOC exhibited higher tumor values, 67 Ga-DATA-TOC cleared faster from background tissues. These findings support the suitability of the newly introduced bifunctional chelator DATA as a reliable, quick and convenient means for labeling medically relevant vectors with the PET radiometal 68 Ga.